A STUDY OF THE COMPONENTS OF HAPPINESS AND THE ROLE OF DEMOGRAPHIC VARIABLES AMONG THE STUDENTS AT KERMANSHAH UNIVERSITY OF MEDICAL SCIENCES - Abbasi, Parvin; Timareh, Mehnoosh; Ziapour, Arash; Kianipour, Neda (Journal of Postgraduate Medical Institute, 2018)
Objective: To investigate the components of happiness and the role of de- mographic variables among the students at Kermanshah University of Medical Sciences. Methodology: This was a descriptive study. The study population consisted of 350 students of Medicine, Dentistry and Pharmacology Schools at Kerman- shah University of Medical Sciences in 2016. Sampling was done through simple random sampling. For data collection, a demographic questionnaire and the Argyle's revised Oxford happiness questionnaire (OHQ) were utilized. The data were analyzed through the descriptive (frequency, percentage frequency, mean, and standard deviation) and inferential statistics (ANOVA and t-test) in the sta- tistics software, SPSS version 21.0. Results: Out of 350 subjects, the male population accounted for 170 (48.6%) subjects. The mean age of subjects was 23.14 ±4.70 years. A large proportion of the population, (n=315, 90%) were single, 306 (87.4%) subjects were from the urban areas and 129 (36.9%) of the subjects were residing in dormitories. Academically, 157 subjects (44.9%) were majoring in Medicine and 67 (19.1%) were in their second term. Self-esteem had the highest mean score (3.77 ±0.19) as opposed to subjective well-being with the lowest mean score (1.73 ±0.26). The mean score of students' happiness was 3.68 ±0.13. There were significant relationships between the total score of happiness and each of the demograph- ic variables (gender, age, place of birth, marital status, mode of residence, aca- demic term, and field of study) with p value <0.05. Conclusion: The students' happiness at Kermanshah University of Medical Sci- ences correlated with gender, age, place of birth, marital status, mode of resi- dence, academic term and field of study.